The use of the multidimensional protein identification technology (MudPIT) to analyze plasma proteome of astronauts collected before, during, and after spaceflights. (April 2022) - Martin, D.; Makedonas, G.; Crucian, B.; Peanlikhit, T.; Rithidech, K.
Abstract: We applied one of the highly sensitive proteomic approaches, i.e. the Multidimensional Protein Identification Technology (MudPIT), to determine protein alterations, qualitatively and quantitatively in plasma samples collected before, during, and after spaceflights from the same astronauts. These plasma samples were prepared from blood drawn in acid-citrate dextrose (ACD) tubes. Samples from four recruited astronauts were available for analysis. There were two sampling time-points for each stage of the spaceflight, resulting in six blood samples from each astronaut for analysis. The results would help to identify proteins that are candidates for functional roles in response to spaceflight or re-adaptation to the earth's environment. The in-flight duration for each astronaut was 6 months. A total of 453 unique and non-redundant proteins were identified at > 99% confidence. We found 19 proteins with significantly altered expression due to spaceflights. These include lumican, extracellular matrix protein 1, vitronectin, filaggrin-2, ceruloplasmin, desmoplakin, antithrombin-III, fibronectin, protein disulfide-isomerase A3, titin, tropomodulin-3, zyxin, bridging integrator 2, apolipoprotein A-II, platelet factor 4 variant, beta-Ala-His dipeptidase (or carcinosine dipeptidase), alpha-2-HS-glycoprotein, pigment epithelium-derived factor, and CD5 antigen-like. These proteins are involved in inflammatory responses, the cytoskeleton system, and metabolism. The MudPIT method also allows the detection of several low-abundance proteins in astronauts' plasma that have not been reported. Importantly, such low-abundance proteins may potentially have functional roles in response to spaceflight or re-adaptation to the earth's environment. Our results provide a significant foundation for future studies in a larger cohort of astronauts that will increase our knowledge of space biology and enable the future development of countermeasures. Highlights: Analysis of four astronaut proteomes before, during and after 6 month ISS mission. Nineteen plasma proteins with significantly altered expression were detected. Individual variations in the expression levels of these proteins were found. The proteins are involved in inflammatory responses, cytoskeleton, and metabolism. First time detection of several low-abundance proteins in ISS astronauts' plasma.